Use of Reasonable Land in Developing Gourami Fish Cultivation for the People of Karangeger Pajarakan Village - Totok Harianto; Abdul Komar; Abdul Hamid (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2024)
This study aims to build the economy in the village mastarakat Karanggeger Pajarakan Probolinggo in an effort to improve the welfare of the community, welfare will be realized if the community's income increases. One of them is entrepreneurship through the empowerment of Gourami ponds which is expected to increase people's income. The method used is the ABCD (Asset Based Community Development) approach with emphasis on empowerment, understanding the potential and challenges to improve the quality of individuals and groups. The result of this community service is in community empowerment through the development of aquaculture with ABCD approach to the community or residents, the authors found that the fish pond asset is very promising to improve the economy of the community, so that people know this in order to design the design as well as possible in accordance with the instructions of the fisheries office. Gourami fish management has been done starting with seeding as many as 10 thousand fish that will be harvested within the next 8-12 months.